Self-Correction for Eye-In-Hand Robotic Grasping Using Action Learning - Muslikhin; Jenq-Ruey Horng; Szu-Yueh Yang; Ming-Shyan Wang (IEEE Access, 2021)
Robotic grasping for cluttered tasks and heterogeneous targets is not satisfied by the deep learning that has been developed in the last decade. The main problem lies in intelligence, which is stagnant, even though it has a high accuracy rate in usual environment; however, the cluttered grasping environment is very irregular. In this paper, an action learning for robotic grasping using eye-in-hand coordination is developed to grasp the cluttered and wide range of various objects using 6 degree-of-freedom (DOF) robotic manipulator equipped with a three-finger gripper. To involve action learning in this system, k-Nearest Neighbor (kNN), Disparity Map (DM), and You Only Look Once (YOLO) were needed. After successfully formulating the learning cycle, an instrument assesses the robot’s environment and performance with qualitative weightings. Some experiments of measuring the depth of the target, localization of target variations, target detection, and the gripping process itself were conducted. The entire process is spread out in plan, act, observe, and reflect for each action learning cycle. If the first cycle does not suffice the results according to the minimum pass standard, the cycle will renew until the robot succeeds in picking and placing. Furthermore, this study demonstrated that the action learning-based object manipulation system with stereo-like vision and eye-in-hand calibration can improve intelligence over previous errors with acceptable errors. Thus, action learning might be applicable to other object manipulation systems without having to define the environment first.